Pelatihan Budidaya Ikan Dalam Ember Bagi Anggota Pimpinan Daerah Nasyiatul Aisyiyah (PDNA) Banyumas - Muhammad Azharul Rijal; Ikhsan Pratama; Susanto Susanto; Puji Utami (JURNAL KASTARA, 2025)
The Regional Leadership of Nasyiatul Aisyiyah (PDNA) Banyumas is an organization belonging to the Muhammadiyah organization which focuses on young women and young women. The age limit for PDNA administrators is 40 years. In Banyumas there are 27 Nasyiatul Aisyiyah (PCNA) Branch Leaders. This effort to transfer fish farming technology in buckets seeks to increase food security and household scale food independence efforts for Banyumas Regency PDNA administrators. Cultivation in buckets is an easy and environmentally friendly cultivation activity so it is very easy for housewives to do. This activity is carried out using direct outreach and training methods. As a result of this training, PDNA members carried out the training well and ended with a training evaluation. Harvesting of kale and catfish was carried out in the third month after training. We would like to thank LPPM UMP for providing financial assistance so that this activity successfuly.